2012
DOI: 10.1080/10810730.2011.635767
|View full text |Cite
|
Sign up to set email alerts
|

Health Locus of Control, Acculturation, and Health-Related Internet Use Among Latinas

Abstract: Among individuals residing in the United States, the Internet is the third most used source for obtaining health information. Little is known, however, about its use by Latinas. To understand health-related Internet use among Latinas, the authors examined it within the theoretical frameworks of health locus of control and acculturation. The authors predicted that acculturation would serve as a mediator between health locus of control and health-related Internet use, age and health-related Internet use, income … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 20 publications
2
22
0
1
Order By: Relevance
“…For instance, foreign born, low income, and Spanish-language dominant Latinos are more likely to rely on television, family, and friends for health information rather than medical providers. 58, 59 Thus, interventions need to be tailored to address language and literacy levels, unique illness beliefs and attitudes (Table 2), as well as educational and shared decision making models that incorporate family members and friends. For example, a qualitative study of Latinos with diabetes and their family members in Chicago found that participants were most interested in peer-based diabetes self-management interventions in a group setting rather than a telephone-based one-to-one peer program.…”
Section: Tailoring Ehealth Interventions For Latino Populationsmentioning
confidence: 99%
“…For instance, foreign born, low income, and Spanish-language dominant Latinos are more likely to rely on television, family, and friends for health information rather than medical providers. 58, 59 Thus, interventions need to be tailored to address language and literacy levels, unique illness beliefs and attitudes (Table 2), as well as educational and shared decision making models that incorporate family members and friends. For example, a qualitative study of Latinos with diabetes and their family members in Chicago found that participants were most interested in peer-based diabetes self-management interventions in a group setting rather than a telephone-based one-to-one peer program.…”
Section: Tailoring Ehealth Interventions For Latino Populationsmentioning
confidence: 99%
“…Information seeking may further vary across specific obesity-related behaviors. Most extant studies of information seeking among Latinos have utilized survey data to quantitatively examine information-seeking behaviors 1821, 2326 but have not included qualitative data to explore more nuanced aspects of information seeking. For example, there is little information about whether Latino parents actively seek or are passively exposed to different types of health information and how these 2 types of exposures affect interest or trust in information obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Immigrant health research has investigated a wide range of topics from youth substance use [42, 43], prescription drug information [44] to cancer information seeking behaviors [45, 46]. To solve various health concerns of the under-represented population, one must acknowledge that acculturation plays a critical role in immigrants’ health status as well as their communication and comprehension of health information [47].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies note that language preference in interpersonal communication predicted the intention to use the Internet [45] and the actual use of the Internet among Latino immigrants when seeking health information [45]. …”
Section: Introductionmentioning
confidence: 99%